Hope - "Harvey, Andrew" (New Delhi, 2010)
In The Hope, Andrew Harvey offers not only a guide to discovering your divine purpose but also the blueprint for a better world. It consists of the necessary elements that can inspire greatness in each of us. Based on Harvey$1 (Bs concepts of Sacred Activism, a global initiative designed to save the world from its downward spiral of greed, pain, and self-destruction, the book is an enlightening text that reflects our world today, while in turn, shapes our future. There are seven laws of Sacred Activism that have the potential to transform our world. Each law, in its own unique way, promotes love above all other impulses. Sacred Activism is about finding gratitude, forgiveness, and compassion; it is about opening yourself up to the kindness within you, letting go of pain, and making a conscious choice to help heal the world. Learn how to incorporate a spiritual practice into your life, transform anger into positive energy, and take part in a global community. Reclaim a world that for too long has been driven by selfishness and hatred. Discover the infinite joy of giving. Turn away from everything you have been and done and believed, and dive into the consciousness of a divine love that embraces all beings. While the future may appear bleak, The Hope provides practical advice to all those who want positive change.s
Keywords: Mind